7(r-4)-(-4+4r)=-r+4+2r

Simple and best practice solution for 7(r-4)-(-4+4r)=-r+4+2r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(r-4)-(-4+4r)=-r+4+2r equation:


Simplifying
7(r + -4) + -1(-4 + 4r) = -1r + 4 + 2r

Reorder the terms:
7(-4 + r) + -1(-4 + 4r) = -1r + 4 + 2r
(-4 * 7 + r * 7) + -1(-4 + 4r) = -1r + 4 + 2r
(-28 + 7r) + -1(-4 + 4r) = -1r + 4 + 2r
-28 + 7r + (-4 * -1 + 4r * -1) = -1r + 4 + 2r
-28 + 7r + (4 + -4r) = -1r + 4 + 2r

Reorder the terms:
-28 + 4 + 7r + -4r = -1r + 4 + 2r

Combine like terms: -28 + 4 = -24
-24 + 7r + -4r = -1r + 4 + 2r

Combine like terms: 7r + -4r = 3r
-24 + 3r = -1r + 4 + 2r

Reorder the terms:
-24 + 3r = 4 + -1r + 2r

Combine like terms: -1r + 2r = 1r
-24 + 3r = 4 + 1r

Solving
-24 + 3r = 4 + 1r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-1r' to each side of the equation.
-24 + 3r + -1r = 4 + 1r + -1r

Combine like terms: 3r + -1r = 2r
-24 + 2r = 4 + 1r + -1r

Combine like terms: 1r + -1r = 0
-24 + 2r = 4 + 0
-24 + 2r = 4

Add '24' to each side of the equation.
-24 + 24 + 2r = 4 + 24

Combine like terms: -24 + 24 = 0
0 + 2r = 4 + 24
2r = 4 + 24

Combine like terms: 4 + 24 = 28
2r = 28

Divide each side by '2'.
r = 14

Simplifying
r = 14

See similar equations:

| (5x-7)(2x+1)-10x(x-4)=0 | | 3y=2y-5 | | f+f+f= | | 6v+18=35t | | d*d= | | (b+2)[(b+3)x-7]=b^2+4b+4-2b | | 4acosx=a+1 | | ln(2x^2+9x-5)=1+ln(x^2+2x-15) | | 15=-d+20 | | y(y+8)= | | 8n+1-6n+5=-4(-6-3n)-8(-1+n) | | -98k=7+4k | | 5n-25+4=8n+3 | | 5+3r=5r+12 | | -6y-3=3-3y | | 2=35x-13 | | 19x+26=121 | | 4t-6=5(t+5) | | 19x+26=21 | | 4n-12=13-4n | | 13x-2(3x+6)= | | -8n+12=-4n-4 | | 2n^2+11n+10=0 | | r^2-8r-20=0 | | 7-7=18x+8x | | 3(x+8)=3x+12 | | x/2=-30+35 | | 3x+4x^2=56 | | -4+10=12x-5-11x | | 3(v-2)-5v=-2(v+2) | | 3(2x-5)=7(x+2) | | v^2+6v-7= |

Equations solver categories